2021
DOI: 10.1186/s12889-021-11893-4
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the direct Covid-19 disability-adjusted life years impact on the Malta population for the first full year

Abstract: Background Disability-adjusted life years (DALYs) combine the impact of morbidity and mortality, allowing for comprehensive comparisons of the population. The aim was to estimate the DALYs due to Covid-19 in Malta (March 2020–21) and investigate its impact in relation to other causes of disease at a population level. Methods Mortality and weekly hospital admission data were used to calculate DALYs, based on the European Burden of Disease Network co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
62
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(76 citation statements)
references
References 20 publications
1
62
3
1
Order By: Relevance
“…(20,22) Studies of approximately 1 year duration completed in Germany, Scotland, and Malta estimate DALYs of 305,641, 96,519 and 5,478 respectively. (24,25,23)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(20,22) Studies of approximately 1 year duration completed in Germany, Scotland, and Malta estimate DALYs of 305,641, 96,519 and 5,478 respectively. (24,25,23)…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to findings in South Korea and the United States with YLL per death of 9.46 and 9.23 respectively, (20,21) however, other national BoD studies indicated YLL per death ranging from 4.79 to 15.79. (22,23) Variation in YLL per death across studies is influenced by which life valuation table is applied. Despite extensive population health interventions designed specifically to reduce the risk of COVID-19, deaths directly related to the virus are likely to rank second when compared to RoI 2019 mortality data.…”
Section: Discussionmentioning
confidence: 99%
“… Nil Nil Asymptomatic Not considered Nil Nil Moderate Calculated based on the reported symptomatic infections minus the Ward admission and ICU admission reported in Table ES1, ES2, 2.3 and 2.4 from Doherty Modelling report [ 6 ]. 14 days [ 17 ] 0.051 (0.032 – 0.074) a [ 10 , 11 ] Severe Reported in Table ES1, ES2, 2.3 and 2.4 from Doherty Modelling report [ 6 ]. 14 days [ 17 ] 0.133 (0.088 – 0.190) a [ 10 , 11 ] Critical Reported in Table ES1, ES2, 2.3 and 2.4 from Doherty Modelling report [ 6 ].…”
Section: Methodsmentioning
confidence: 99%
“… 14 days [ 17 ] 0.051 (0.032 – 0.074) a [ 10 , 11 ] Severe Reported in Table ES1, ES2, 2.3 and 2.4 from Doherty Modelling report [ 6 ]. 14 days [ 17 ] 0.133 (0.088 – 0.190) a [ 10 , 11 ] Critical Reported in Table ES1, ES2, 2.3 and 2.4 from Doherty Modelling report [ 6 ]. 14 days [ 17 ] 0.655 (0.579 – 0.727) a [ 10 , 11 ] Post-acute consequences (ONS) Start at 25.91% (23.2 to 29.0%) 2 weeks after initial COVID infection [ 18 ] a See notes below on how we compute for the COVID-19 survivors noted in this calculation.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, there is no doubt that the COVID-19 pandemic is the most severe public health crisis for all countries and regions of the world [ [1] , [2] , [3] ]. From the central government to the local governments at all levels in the mainland of China adopt strong preventive measures [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%